Body story - Williams, David; Klein, Leanne; Films for the Humanities (Firm); Discovery Channel (Firm); Wall to Wall Television (London : Wall to Wall Television Ltd. ; Macmillan, Films for the Humanities & Sciences, 1998)
This program follows each stage of John's heart attack, from the rupture of a coronary plaque, to dissolving the resulting clot, to ventricular defibrillation, to recovery
Glossary
Bibliography
VHS
Keywords: Cardiac arrest; Hypercholesteremia; Blood cholesterol; Heart -- Disease; Mind and body; Physiology; Cholesterol, Dietary -- adverse effects; Heart Arrest; Heart Diseases -- etiology; Hypercholesterolemia